Recurrent urinary tract infections: Evaluation of the prophylactic efficacy of urinary antiseptics methenamine and methylthioninium chloride - Geller, Mauro; Gama, Carlos Romualdo Barboza [UNESP]; Guimarães, Oscar Roberto; Varella, Rafael Brandão; Oliveira, Lisa; Da Fonseca, Adenilson de Souza; De Paoli, Severo; De Paoli, Flavia (My University, 2008)
Introduction: Urinary tract infection (UTI) is a very common condition in clinical practice, affecting an estimated 50% of all adult women during a lifetime. The most common causative agent is E. coli; UTI may also be caused by S. saprophyticus, Enterobacteria (Klebsiella sp and Serratia sp.), Enterococcus sp., and P aeruginosa. Recurrent UTIs occur at least twice per semester or three times a year. Prophylactic measures to prevent recurrent UTIs include changes in contraception methods, cranberry products, increased fluid intake, urination after intercourse, vaginal estrogen therapy for post-menopausal women, antibiotics, and urinary tract antiseptic agents. Objectives: To evaluate the use of a combination of methenamine and methyl-thioninium chloride in the prophylaxis of recurrent uncomplicated lower UTIs, with respect to: • Signs and symptoms of UTI • Etiologic agent(s) • Recurrence rates • Need for antibiotic therapy in case of recurrence • Incidence of adverse events associated with the treatment, including any reported alterations of laboratory tests Materials & methods: A descriptive, analytic, restrospective study was performed at Hospital Universitário Constantino Otaviano - UNIFESO. Medical charts from patients presenting recurrent uncomplicated lower UTI attended from 2001-present were analyzed, including the following information: Demographic data (age, gender, weight, ethnicity, living conditions): medical history/signs and symptoms of UTI; identification of treatment and dosing regimens; treatment duration; recurrence rates and need for antibiotic therapy in case of recurrence; other medications prescribed; and records of adverse events. Results: E. coli was identified as etiologic agent in 80% of the patients. Following antibiotic therapy, all patients received prophylactic treatment with the combination of methenamine and methylthioninium chloride. Treatment duration ranged from three to six months. Adverse events were observed in 13/60 patients (21.7%). At the end of the respective treatment periods, a statistically significant (p<0.0001) number of patients showed no UTI recurrence. Conclusion: Based on the results from the collected data, we conclude that an orally administered combination of methenamine and methylthioninium chloride is safe and effective in the prophylactic treatment of recurrent uncomplicated lower urinary tract infection. © Copyright Morelra Jr. Editora.
Keywords: Methenamine; Methylthioninium chloride; Prophylaxis; Recurrent urinary tract infection; antiinfective agent; methenamine; methylthioninium chloride; unclassified drug; adult; antibiotic therapy; controlled study; demography; diarrhea; drug dose regimen; dyspepsia; epigastric pain; Escherichia coli; female; headache; human; laboratory test; major clinical study; male; nausea; rash; recurrent disease; retrospective study; treatment duration; urinary tract infection